Impact of fresh grape juice on the pharmacokinetics of omeprazole: results of a food–drug interaction study - Iftikhar, Tayyaba; Iqbal, Zafar; Shah, Yasar; Khan, Nauman Rahim; Abbas, Muhammad; Shehzad, Omer; Hadi, Fazal; Sardar, Haseeba; Abusharha, Ali; Daglia, Maria; Khan, Haroon (Frontiers in Pharmacology, 2024)
Grapes have been reported as seeing wide use for dietary ailments, due to their attributed pharmacological activities. Resveratrol, as the chief constituent of grapes, is responsible for their pharmacological benefits. However apart from their beneficial effects, grapes have also been under consideration in the past few years in drug interaction studies. This study investigated the pharmacokinetic profile of omeprazole administered alone compared to omeprazole administered with grape juice, with a prior intake of grape juice, for one continuous week. The study was conducted on two groups of healthy male volunteers [n=12]. One group was orally administered 40 mg omeprazole alone while the other group was administered omeprazole with grape juice. Blood samples were analysed for omeprazole concentration by a reverse phase HPLC method.Co-administration of 40 mg omeprazole with grape juice significantly decreased the AUC0-t and Cmax by 32% and 34% respectively, suggesting a role being played by grapes in the activation of P-glycoprotein and omeprazole metabolising enzymes including CYP3A4 and CYP2C19. In conclusion, the addition of grapes as a dietary supplement in patients taking omeprazole for management of peptic ulcer symptoms may lead to a higher required dose of omeprazole.